Organizing Institutions To Improve The Performance Of GTK (Teachers And Educational Staff) (Multisite Study At MAN 1 Kota Kediri And MAN 2 Tulungagung) - Bahru Isnaini, Yauma; Tanzeh, Ahmad; Fauziyah Laili, Ummiy (Publisher Cv. Inara, 2025)
This research is motivated by the phenomenon of organizing madrasa institutions aimed at improving the performance of GTK. This research uses a qualitative approach with a multisite design, data collection techniques through in-depth interviews, participant observation, and documentation, as well as cross-site analysis. The research results show that: (1) The organization structure is developed through the internalization of the vision and mission, division of labor, work grouping, line of authority, span of control, centralization, decentralization, and formalization. (2) Job division improves GTK performance through task identification, employee placement according to educational qualifications, and workload according to standard regulations. (3) Delegation of authority is carried out through task identification, assessment of GTK competencies, granting of power, and responsibility. (4) Cooperative relationships are enhanced through good communication, collaboration, trust, and team cohesion in the madrasa. The validity of the data is tested through credibility, transferability, dependability, and confirmability tests. Thus, this research provides an in-depth understanding of how organizational structure, division of labor, delegation of authority, and cooperative relationships can enhance the performance.